Digital Roots Historicizing Media and Communication Concepts of the Digital Age - Schafer, Valérie; Balbi, Gabriele; Ribeiro, Nelson; Schwarzenegger, Christian (Studies in Digital History and Hermeneutics, 2021)
Several of the most known and discussed concepts of the digital age predated the digitalization itself and have been previously used in the "analogue times". Other concepts were coined for the digital society but have transformed and are continuously transforming over time. This edited book selects some of these concepts and starts a time travel through their history, heritage, reinvention, and reinvestment in media and communication studies.